Analisis Kebijakan Larangan Study Tour dan Dampaknya terhadap Motivasi Belajar Siswa Indonesia - Rakha Putra Setya; Najwa Fithriyah; Naya Aranti Fitri; Syarifah Nur Kholidah; Suhardi Suhardi (Badan Penerbit STIEPARI Press, 2025)
This research is motivated by the limited study of the impact of the study tour ban policy in Indonesia, even though this phenomenon has significant implications for the educational, economic, and social ecosystem. Study tours have been considered as one of the experiential learning methods that provide direct experience to students to understand learning materials in a real context. However, with the prohibition policy, there has been a drastic change in the dynamics of teaching and learning activities, especially in terms of student learning motivation. This study aims to comprehensively analyze the positive, negative, and unexpected impacts of the implementation of the study tour ban policy. The research method used is descriptive qualitative with a literature review approach. Various secondary sources, such as journal articles, news, policy reports, and related publications, were systematically analyzed using the education policy analysis framework. The results of the study show that this policy has a positive side, such as improving student safety and reducing the financial burden of parents. However, on the other hand, this policy also reduces students' opportunities to learn outside the classroom, limits access to authentic learning resources, and decreases motivation to learn due to the loss of the hands-on experiential learning aspect. In addition, unexpected impacts were also found, such as the weakening of the local tourism sector which has been a study tour destination, as well as the emergence of learning innovations based on local wisdom as a form of adaptation. The main conclusion of this study is that the policy of total ban on study tours is only a partial solution that causes a trade-off between pragmatic safety and pedagogical quality. Therefore, it is recommended that this policy be transformed into strict regulations with safety, risk management, and affordable cost standards so that the student learning experience remains optimal.